The challenges to performance and sustaining mutual health organisations/health institutions: An exploratory study in Ghana - Adomah-Afari, A. (International Journal of Health Care Quality Assurance, 2015)
Purpose – The purpose of this paper is to explore challenges to the performance and sustainability of mutual health organisations (MHOs) and health institutions towards enhancing access to quality health care (HC) in Ghana. Design/methodology/approach – Data were gathered through interviews and documentary review. Findings – Problems with late release of reimbursement funds for discharging with claims by the central government has impacted heavily on the financial and strategic management and decisionmaking processes of the MHOs and health institutions. Research limitations/implications – The lack of in-depth analysis of the financial viability of the MHOs; and the limited number of schemes selected. Practical implications – Recommends the need to ensure prompt release of reimbursement funds by government to enable the MHOs to reimburse claims to health institutions. Social implications – There is a perceived tension between the MHOs and HC institutions due to late release of reimbursement funds by the government. Originality/value – Contributes to understanding of how the NHI Act influences the operations of MHOs and health institutions towards increasing access to quality HC and financing. © 2015, Emerald Group Publishing Limited.
Keywords: Effectiveness; Efficiency; Finance/economics; Patient perception; Quality health care; Risk management